Beban Kerja Tubuh Manusia menggunakan Metode Recommended Weight Limit dan Lifting Index - Dedi Lesmana (Universitas Putra Indonesia YPTK Padang, 2022)
The purpose of this study is to determine the factors that affect movement, correct body posture in doing work so that injuries do not occur at work and the maximum load that can be lifted by workers. The case study was conducted in a rubber processing industry The calculation of the Recommended Weight Limit (RWL) for each worker in the lifting of rubber raw materials and lifting to weighing has a weight range of 30-50 kg in each lift. Documentation results obtained from horizontal distance (H), vertical distance (V), asymmetric angle (A), load starting point (D), number of loads lifted per minute (F), moment of force (C). In the results of the RWL calculation, the recommended weight of the load is between 11.06 kg and 21.24 kg. The recommended weight of the load for workers in the lifting of rubber raw materials and lifting to weighing is based on the calculation of the Recommended Weight Limit (RWL), the level of risk based on the provisions of the National Institute of Occupational Safety and Health (NIOSH) Lifting Index is that the effect of back injury is still identified when viewed from the calculation results of the Lifting Index (LI) value. The LI value for workers is more than 1 (one) so it needs immediate repair. Workload solutions that can be applied to the lifting of rubber raw materials and lifting to weighing are reducing the weight of the load and improving work methods.